2018
DOI: 10.1155/2018/3487183
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Artesunate-Amodiaquine on Schistosoma mansoni Infection among Children Infected by Plasmodium in Rural Area of Lemfu, Kongo Central, Democratic Republic of the Congo

Abstract: Background Malaria and schistosomiasis remain life-threatening public health problems in sub-Saharan Africa. The infection pattern related to age indicates that preschool and school-age children are at the highest risk of malaria and schistosomiasis. Both parasitic infections, separately or combined, may have negative impacts on the haemoglobin concentration levels. The existing data revealed that artemisinin derivatives commonly used to cure malaria present also in antischistosomal activities. The current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
7
2
Order By: Relevance
“…Pyronaridine has an estimated terminal elimination half-life of around 14 days [39] in contrast to artesunate with approximately 1 h [40]. Clinical trials testing mefloquine [41] and ACTs like artesunate-amodiaquine [42], artesunate-sulfalene-pyrimethamine, or artemether-lumefantrine [43,44] in patients concomitantly infected with P. falciparum and Schistosoma spp. reported a beneficial secondary antischistosomal efficacy, e.g.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Pyronaridine has an estimated terminal elimination half-life of around 14 days [39] in contrast to artesunate with approximately 1 h [40]. Clinical trials testing mefloquine [41] and ACTs like artesunate-amodiaquine [42], artesunate-sulfalene-pyrimethamine, or artemether-lumefantrine [43,44] in patients concomitantly infected with P. falciparum and Schistosoma spp. reported a beneficial secondary antischistosomal efficacy, e.g.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The combination treatment was administered for three days, with more adverse events expected due to longer treatment duration, and drug-drug interactions. In previous studies, fewer adverse events were observed in the ACT group than in the PZQ group [1012,14].…”
Section: Discussionmentioning
confidence: 88%
“…N. El‐Beshbishi also found that the artemisinin–naphthoquine phosphate combination showed an outstanding effect on the Egyptian strain of S. mansoni and was able to kill all parasites at a dosage of 40 or 20 μg/ml within 48 or 72 h 50 . Meanwhile, synergistic effects of artesunate‐amodiaquine that could significantly kill S. mansoni in children were also observed in a clinical study 51 …”
Section: Antiparasitic  Activities Of Artemisininsmentioning
confidence: 83%